Board of Commissioners’s Characteristics (Size, Independence, Expertise) and Financial Reporting Quality - Kusumawardani, Media; Yanto, Desri (Akuisisi : Jurnal Akuntansi, 2023)
The quality of financial reports is necessary for the users. Factors that can improve the quality of financial reports that can be proven true are things that need to be prioritized. So research is needed that can prove the factors involved. This study aims to test the board of commissioners as a party that has a role in a company. The board of commissioners is the party that supervises a company entity and ensures that the committee carries out audits. In this study, the board of commissioners becomes an independent variable seen from the size, independence, expertise with leverage control variables, audit quality, company size, company growth. The object of this research is a manufacturing company listed on the Sharia Securities List in 2018-2020. The sample used is 198 companies that filled the requirement. The sample collection method used a purposive sample. The type of data used is secondary data and the data processing tool uses SPSS. In this study, the Board of Commissioners (Size, Independence, Expertise) were not proven to influence the Quality of Financial Statements. While the control variables in this study showed a positive influence in addition to the leverage variable, namely audit quality, company size, and company growth. So it can be concluded that all hypotheses in this study were rejected. So based on the point of size, independence, and expertise of the board of commissioners in this study, it does not have a large enough role in determining the Quality of Financial Statements.